An overview of radiolabeled amino acid tracers in oncologic imaging - Jain, Sanchay; Dhingra, Vandana Kumar (Frontiers in Oncology, 2023)
Molecular imaging has witnessed a great progress in the field of oncology over the past few decades. Radiolabeled amino acid (AA) tracers are particularly helpful in the areas where the utility of 18F-Fluorodeoxyglucose (18F-FDG) positron emission tomography with computed tomography imaging has been limited such as in evaluating brain tumors, neuroendocrine tumors (NETs), and prostate cancer. Radiolabeled AA tracers such as 6-[18F]-L-fluoro-L-3, 4-dihydroxyphenylalanine (18F-FDOPA), 18F-fluoro-ethyl-tyrosine (18F-FET), and 11C-methionine have found wide applications in brain tumors, which, unlike 18F-FDG, concentrate in the tumor tissue to a greater extent than that in normal brain tissue by providing accurate information about tumor volume and boundaries. 18F-FDOPA is also useful in evaluating NETs. Tracers such as 18F-FACBC (Fluciclovine) and anti-1-amino-2-[18F]fluorocyclopentyl-1-carboxylic acid (18F-FACPC) are used in imaging of prostate cancer and provide valuable information of locoregional, recurrent, and metastatic disease. This review highlights AA tracers and their major applications in imaging, viz., in evaluating brain tumors, NETs, and prostate cancer.